Membangun Server Multicast Berbasis Streaming Menggunakan Centos - Irwan Susanto; Rizky Junita Sari (JURNAL INFOTEL, 2009)
The development of IP-based technology contribute to the development of telecomunication and information technology. One of IP-based technology application is streaming multicast, as part of broadcasting. The streaming process is made by accessing Telkom-2 broadcast through AKATEL LAN network, then server forward it to clients using multicast IP system. Multicast IP is D-class IP, which is able to send data package in realtime. In multicast system, server only send one data package to some clients with same speed transmition. The Telkom-2 broadcast is already accessed before sent as data package. Server will access Telkom-2 broadcast using parabola antenna and Hughes modem, then forward it to clients through AKATEL LAN network. Clients must conect to server via AKATEL LAN network and already instaled VLC player, in order to be able to access the Telkom-2 broadcast